Characterization and Patterns of Conformation, Evolution and Consolidation of Housing in Informal Andean Settlements: the Case of Pomachaca, Tarma, Peru - Espinoza Carrion, Julissa Raquel (2024)
The increase in informal settlements has aroused the concern of many professionals and governments seeking to understand the emergence and expansion of these dwellings, as they currently coexist and form an integral part of our cities, especially in less developed countries, where high rates of urban expansion are often associated with the emergence of informal settlements. As a consequence, the resistance and proliferation of these settlements have become a phenomenon, in which state intervention has failed to curb their growth. This article seeks to identify those recurrent patterns that allow the conformation, evolution and consolidation of informal settlements based on evidence from the Pomachaca human settlement in the Andean city of Tarma. The methodology developed is based on a structured visual survey analyzing 224 lots, 128 informal and 96 formal. As a result, in the first place, the spatial logic to build their houses in the territory is recognized, taking into account the urban circumstances. Secondly, the orders that adapt informal dwellings in relation to their direct formal environment or to the informal user's own spatial conceptions are identified and finally 3 adaptations are determined: (i) the combination of natural environment and building, (ii) the north-south location along the street and (iii) the blend of construction materials according to the user's economy. Therefore, the research concludes that informal settlements prove to be a valuable form of urban development as they employ spatial practices and improvements that contribute to the informal settlement becoming a dynamic and discrete entity, in a state of continuous change with its own spatial characteristics.